2022
DOI: 10.3390/ijms23158190
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Characterization, and Expression Analysis Related to Low-Temperature Stress of the CmGLP Gene Family in Cucumis melo L.

Abstract: Germin-like protein (GLP) participates in plant growth and development and plays an important role in plant stress. In the present study, 22 CmGLPs belonging to five classes were identified in the melon genome. Each member of the CmGLPs family contains a typical Cupin_1 domain. We conducted a genome-wide analysis of the melon GLP gene family characterization. CmGLPs were randomly distributed in the melon chromosomes, with the largest number on chromosome 8, having eight family members. Gene duplication events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…CDP family includes GLP members that contain a single cupin_1 domain, which are related to hormone-mediated development processes ( Murphy and Peer, 2022 ). GLPs have been identified in multiple species ( Davidson et al., 2010 ; Cheng et al., 2014 ; Li et al., 2016 ; Zhang et al., 2022 ; Li et al., 2023 ), and whole CDP family members have also been identified in B. napus ( He et al., 2022 ). In our cognition, the distribution and functional diversity of CDP family in ma bamboo have not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDP family includes GLP members that contain a single cupin_1 domain, which are related to hormone-mediated development processes ( Murphy and Peer, 2022 ). GLPs have been identified in multiple species ( Davidson et al., 2010 ; Cheng et al., 2014 ; Li et al., 2016 ; Zhang et al., 2022 ; Li et al., 2023 ), and whole CDP family members have also been identified in B. napus ( He et al., 2022 ). In our cognition, the distribution and functional diversity of CDP family in ma bamboo have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The GLP proteins are derived from the tissue-specific posttranslational processing of the proglucagon peptide. For example, GLP proteins in Cucumis melo responded to low temperatures, and CmGLP2-5 may have a key role in this process ( Zhang et al., 2022 ). Overexpression of DIGLP1-5-1 in the globular embryos of Dimocarpus longan increased the accumulation of lignin and lowered the H 2 O 2 content by modulating the activities of ROS-related enzymes ( Li et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Salinity, osmotic stress, MATE heavy metals 7,8 Low temperature 11 CmGLP2-5 Autotoxicity 33 MYB Saline alkali response 33 CmMYB2R40…”
Section: Type Of Abiotic Stress Genes Involvedmentioning
confidence: 99%
“…A genomic study focused on characterizing CmGLP gene family in melon has been found that CmGLP2-5 might be directly associated with low-temperature stress in melon 11 (Table 2). These finding would be helpful in melon molecular breeding programmes for low-temperature stress tolerant cultivars.…”
Section: Type Of Abiotic Stress Genes Involvedmentioning
confidence: 99%
See 1 more Smart Citation